2012
DOI: 10.1074/jbc.m112.373696
|View full text |Cite
|
Sign up to set email alerts
|

Structural Mechanism of ATP-induced Polymerization of the Partition Factor ParF

Abstract: Background: ParF and ParG mediate TP228 plasmid segregation. Results: ATP binding to ParF activates segregation, and ADP binding to ParF antagonizes its segregation function. ParF-ADP is monomeric, and ParF-ATP is dimeric. ParF dimers assemble into polymers. Conclusion: ParF-ATP dimers serve as building blocks for polymer assembly. Significance: ParF-ATP polymers provide a mechanism for plasmid segregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
63
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 36 publications
7
63
1
Order By: Relevance
“…Structures of monomeric ParF bound to ADP recently revealed that the protein adopts an ␣-␤-␣ layered structure with a central sevenstranded ␤-sheet surrounded by several ␣-helices. The adenine nucleotide is situated on the C-terminal side of the parallel ␤-sheets and is recognized by nucleotide-binding motifs including the Walker A box (29). By contrast with ParF-ADP, ParF forms nucleotide sandwich dimers when bound to AMP-PCP.…”
Section: Perturbation Of the Parf Nucleotide-binding Pocket Inducesmentioning
confidence: 99%
See 4 more Smart Citations
“…Structures of monomeric ParF bound to ADP recently revealed that the protein adopts an ␣-␤-␣ layered structure with a central sevenstranded ␤-sheet surrounded by several ␣-helices. The adenine nucleotide is situated on the C-terminal side of the parallel ␤-sheets and is recognized by nucleotide-binding motifs including the Walker A box (29). By contrast with ParF-ADP, ParF forms nucleotide sandwich dimers when bound to AMP-PCP.…”
Section: Perturbation Of the Parf Nucleotide-binding Pocket Inducesmentioning
confidence: 99%
“…This patch inserts into a niche close to the adenine nucleotide-binding pocket of the adjacent subunit in ParF sandwich dimers (29). Considering its location near the Walker A motif in the ParF structure, the P104A change is expected to exert short range impacts on binding pocket conformation (Fig.…”
Section: Perturbation Of the Parf Nucleotide-binding Pocket Inducesmentioning
confidence: 99%
See 3 more Smart Citations